KAJIAN BANGUNAN DI INDONESIA DENGAN AMERIKA (STUDI KASUS RUMAH DI BANTUL) - Adi Setiabudi Bawono (Universitas Negeri Yogyakarta, 2011)
One of the activities of mitigation the earthquake is detect of damage andestimate the probability of building material losses because of earthquake in each typical building on an area. In the developed countries attempt to predict the probability of damage to the building caused by the quake has been a lot done. One method used is HAZUS Method (Hazard United States). In evaluating the damage to buildings, one method is used assessing HAZUS level the probability of damage to each building. This study is an initial study to compare building in Bantul-Indonesia and United State Of America.The Data collected includes the characteristic of houses. Conclusion obtainedfrom this research is that house in bantul different with HAZUS type of building.